Direct Hydroxylation of Benzene to Phenol Over Pyridine-Modified Vanadium-Substituted Heteropoly Acid Under Microwave Condition - Liu, T.; Hou, J.H. (Asian Journal of Chemistry, 2014)
Direct oxidation of benzene to phenol over Py3PMo11V and hydrogen peroxide as the oxidant under microwave irradiation. Pyridine(Py)-modified vanadium substituted heteropoly acid (Py3PMo11V) with Keggin structure was prepared and characterized by FT-IR. The influence of different reaction conditions, such as the reaction time, the amount of catalyst used, the amount of hydrogen peroxide used and the reaction temperature on the yield of phenol was studied to obtain the optimal reaction conditions for phenol formation. Coupled conventionally heated method gives phenol yield of 7.8 %, higher phenol yield of 24.7 % and selectivity of 100 % are obtained when irradiated with microwave energy.